(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of experiments, a study on the effectiveness of the process of displacement and clarification of water. The shape, the study of the cross-section of the mixer, and the design of the mixer have a significant influence.